Harvester perceptions of climate vulnerability: Contributions to building climate resilient fisheries - Runnebaum, Jocelyn M.; Nelson, Laura K.; Harper, Sarah J.; Bell, Richard J.; Smith, Geoffrey S.; Cullen, Alison C.; Cutler, Matthew J.; Levin, Phillip S. (Frontiers in Marine Science, 2023)
The uncertainty of future ocean conditions caused by climate change challenges the conventional fisheries management model that assumes resource extraction occurs in a steady-state environment. As managers respond to climate impacts and focus on long-term preparedness, an overarching goal is to minimize the vulnerability of fishing businesses and communities. However, during the adaptation process, challenges can arise when perceptions of climate change vulnerability differ among scientists, managers, and harvesters. A harvester’s perception of their risk to climate change influences their willingness to plan for and respond to change, yet these views are often overlooked in adaptation planning. To better understand this dynamic, we conducted a regional survey to evaluate the perceptions harvesters hold regarding the impacts of climate change on commercially fished species in the Northeastern United States and the resulting risks from those changes. The waters in this region of the Northwest Atlantic shelf are warming faster than the global average resulting in shifting distributions of species, altered seasonal migrations, and changes in productivity. Respondents’ perceptions aligned with an analysis conducted by scientists on the directionality of climate impacts for 12 out of 27 (44%) of the most commercially important species in the region. Additionally, an understanding of the variability in perceptions of climate change vulnerability emerged: 72% of respondents believe climate change is occurring, 53% believe climate change will harm them personally, and 28% have already seen a negative impact on their ability to catch fish. Respondents who believe that climate change is occurring had higher perceptions of vulnerability on average than those who do not believe it is occurring. Despite a sense of vulnerability to climate change, respondents did not rank it among the top three concerns (fisheries regulations, market access, and access to working waterfronts) for their fishing businesses. Investigating harvester’s perceptions is an opportunity to share their experiences and understand the diversity of perspectives regarding the impacts of climate change. Increasing the inclusion of social science indicators and diverse perspectives will increase climate resilience of fisheries management.